PR Promotion Strategy for Ukrainian Pharmaceutical Manufacturers in The EU Market - Mashchenko Sofiia (My University, 2022)
The thesis aims at the theoretical substantiation and development of practical recommendations for PR strategy for Ukrainian pharmaceutical manufacturer Darnitsa in the EU with the employment of country of origin as descriptive property for products. Based on the study results, methodological recommendations have been developed for Darnitsa on formation of a PR strategy and evaluation of proposed project in the course of its implementation.